Selecting Methodologies and Methods- Research Currents Interview: Theopisti Stylianou-Lambert - Stylianou-Lambert, Theopisti (My University, 2024)
An Introductory Guide to Qualitative Research in Art Museums is a practice-based guide that is designed to introduce qualitative research to established and upcoming museum professionals and increase their confidence to conduct this type of research. Highlighting the work of researchers who are studying museums around the world, the book begins by explaining why there is a need for qualitative research in museums. Rowson Love and Randolph then go on to provide guidance, including theories and frameworks, on how to envision a qualitative research project that facilitates meaningful interpretation of visitor experiences. Chapters in the methodology section begin with descriptions of featured qualitative methodologies and will assist readers as they determine which are most appropriate for their projects and as they advocate for their research. The final section will prepare readers still further by demonstrating data analysis and reporting using the examples in the book.
Keywords: methodologies; qualitative research; interview